SUBDUKSI LEMPENG INDO-AUSTRALIA PADA LEMPENG EURASIA DI PANTAI BARAT SUMATERA BARAT - Akmam, Akmam (IAIN Batusangkar, 2011)
Indo-Australian plate subduction on the Eurasian Plate took place on an ongoing and has formed active tectonics and volcanism on Mentawai andSumatrafault. The level of tectonic activity of this region can be learned through activities plate subduction under subduction velocity, angle of subduction and depth of subduction. An objective of fundamental research is to determine the pattern of the Indo-Australian plate subduction on the Eurasian plate. This research uses secondary data records form the earthquake inWest Sumatrain 1900 until 2005 which is available on BMG Padang Panjang. The speed and angle plate subduction are calculated using the formula of Le Pichon. The research shows that the average angle subduction of the Indo-Australian plate on the Eurasian plate and the surrounding area of West Sumatraare 31.330 with a speed relative subduction average of 6.32 cm / year and the velocity of the normal line is 4.93 cm / year.Key words: subduction, plate, indo-australia, eurasia